EXPERIMENTAL STUDY OF PHASE TRAPPING DAMAGE IN LOW PERMEABILITY AND TIGHT GAS RESERVOIR BY USING MALAYSIAN DIESEL OIL AND CONDENSATE - AHMED, ARSHAD (2013)
Tight gas and low permeability reservoirs mostly have problems in terms of significant damages due to low matrix permeability during drilling, completion, stimulation and production. However, they required advanced improvement techniques to achieve flow of gas at optimum rates.Water blocking damage (Phase Trapping) is a form of mechanical formation damage mechanism, which is caused by the filtrate invasion in drilling and liquid leak-off into formation during stimulation operations mostly in fracturing. Water blocking have noticeable impact on total skin factor in the gas reservoirs which tends to reduces relative permeability around wellbore. Proper evaluation of damage and its factors to influen.ced,.its^S£y.erily-is-- essential for prevent from phase trapping damage and optimizing well productivity.